As formas do real: a representação da cidade em Eles eram muitos cavalos - Rejane Cristina Rocha (Estudos de Literatura Brasileira Contemporânea)
This work discusses the way by which the modern representation of city can be recognized, specially how it concerns to the choice of themes and to the formal options, in a Brazilian contemporary novel: Eles eram muitos cavalos, published by Luiz Ruffato in 2001.